Chronic Venous Disease Management Update - Khan, Md Saif Ullah; Safiuddin, Mohammad; Rahman, Md Mahbubur (University Heart Journal, 2012)
Not available DOI: http://dx.doi.org/10.3329/uhj.v8i1.11666 University Heart Journal Vol. 8, No. 1, January 2012